An evaluation on antinociceptive effects of eugenol by formalin test in rats - Zarifkar A. Assistant Professor; Skandaryan HMS; Mokhtary M. Assistant Professor; Ay J. Assistant Professor (Tehran University of Medical Sciences, 2003)
Statement of Problem: Eugenol is the most important chemical compound of the clove tree (Eugenia aryophylata) extract. That is widely used in dentistry as a bactericidal and pain relieving agent. Aim: The aim of the current study was to evaluate the antinociceptive effect of local and systemic administration of eugenol by formalin test in rats."nMaterials and Methods: In this research, 56 male Wistar rats, weighing 230±20 g were divided into seven groups (n=8). Ten minutes before formalin test, different doses of eugenol (12.5,25,50 mg /in groups 2,3,4 respectively) were injected to the right hind paw of the rats subcutaneously. In- group 5 eugnol (50 mg) was. injected to the contralateral hind paw. In group 6 eugenol (100 mg/ kg) and control group (group 7), equal volume of norma! saline was injected intraperitonealy . The minutes 0-5 and 16-60 were considered as acute and chronic phases of pain in the formalin test, respectively. Data were statistically analyzed by ANOVA and Tukey's tests."nResults: The results showed that local injection of eugenol to the same paw receiving formalin caused a decrease of nociception in both acute and chronic phases of formalin test (PO.005). However, in the group that eugenol (50mg/ kg) was injected to the contralateral paw, no significant differences were observed in the pain score in comparison with the control group. Intraperitoneal injection of eugenol (lOOmg/kg) did not reduce the nociception in the acute phase, but it caused a significant decrease of nociception in tonic phase (PO.00I)."nConclusion: It was concluded that eugenol, as a local anesthetic drug not only inhibits nociceptive impulse conduction on the peripheral pain fibers, but also centrally reduce chronic pain.